Analysis of Wellbore Skin Samples—Typology, Composition, and Hydraulic Properties. Issue 5 (28th January 2016) - Houben, Georg J.; Halisch, Matthias; Kaufhold, Stephan; Weidner, Christoph; Sander, Jürgen; Reich, Morris
Abstract: The presence of a wellbore skin layer, formed during the drilling process, is a major impediment for the energy‐efficient use of water wells. Many models exist that predict its potential impacts on well hydraulics, but so far its relevant hydraulic parameters were only estimates or, at best, model results. Here, we present data on the typology, thickness, composition, and hydraulic properties obtained from the sampling of excavated dewatering wells in lignite surface mines and from inclined core drilling into the annulus of an abandoned water well. Despite the limited number of samples, several types of skin were identified. Both surface cake filtration and particle straining in the aquifer occur. The presence of microcracks may be a determining feature for the hydraulic conductivity of skin layers. In the case of the well‐developed water supply well, no skin layer was detected. The observed types and properties of wellbore skin samples can be used to test the many mathematical skin models. Abstract : Article impact statement : The first in‐depth analysis of wellbore skin types and properties allows testing the many available mathematical models.